FT-IR, Raman, and NMR Spectroscopy and DFT Theory of Glimepiride Molecule as a Sulfonylurea Compound - Ozdemi, T.; Gokce, H. (Springer, 2018)
The glimepiride molecule was experimentally characterized using vibrational (FT-IR and laser-Raman) and NMR chemical shift spectroscopy. The molecule optimized structure, vibrational wavenumbers, and H-1 and C-13 NMR isotropic chemical shifts were theoretically obtained with the DFT/B3LYP method at a 6-311++G(d,p) basis set. The theoretical geometric parameters, vibrational wavenumbers, and NMR che mical shifts were found to be consistent with experimental data and similar spectral results in the literature.
Keywords: Glimepiride; Vibrational Spectrum; H-1 And C-13 Nmr Chemical Shifts; Dft/B3lyp/6-311++G(D,P) Level